Constitutional Principles and Executive Procedures for Forming the Regions in Iraq: Analytical Study - Abdul Fattah Abdul Razaq; Soran Ali Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Fundamental changes happened to the political and constitutional system of the Iraqi State after toppling of the Previous Regime on 9 April 2003, issuing of the Law of Administration for the State of Iraq for the Transitional Period in 2004, and then issuing the Constitution of the Iraqi Republic in 2005. These fundamental changes include all state agencies and the political system, in forefront of which were changing of unified form of the Iraqi State and adopting the federal system, which the Republic of Iraq became a federal state after it was a simple state for a period of more than eighty years since it’s establishing. Since the federal state consists of several regional political units, the change in the number of constituent units of the federal states and their borders is one of the difficult issues that these countries may face, because it may affect the characteristics of the federal system and political stability in federal country. Therefore, it can be found that the federal states frequently resolve them at the beginning through agreement upon in federal constitution, or it might be subject to the agreement of the federal units, or it may require a general referendum to approve it. But, changing the constituent units of federalism in Iraq in terms of their number and border is limited to forming new regions and joining to the formed (existing) regions, and in both cases changing the borders and number of governorates and regions are resulted. This research titled (the constitutional principles and executive procedures for forming the regions in Iraq) addresses the constitutional principles and legal regulation for changing the constituent units of the federal system in Iraq and the needed executive procedures for them. Therefore, according to a digital scientific plan this paper is divided into two parts, the first part deals with the constitutional principles established within The Administration Law of the Iraqi State for the Transitional period of 2004 and the Constitution of the Iraqi Republic of 2005, and some suggestions are provided for the regions in that period. The second part studies the provisions of the Executive Procedures Law regarding the formation of regions No. 13 of the Year 2008.